A Case of Childhood COVID-19 Infection with Pleural Effusion Complicated by Possible Secondary Mycoplasma Pneumoniae Infection. Issue 7 (July 2020) - Chen, Hong-Rui; Zou, Hao; Xue, Mei; Chen, Zhen-Bing; Chen, Wan-Xin
Abstract : We report a case of childhood coronavirus disease 2019 infection with pleural effusion complicated by possible secondary Mycoplasma pneumoniae infection. Fever and pulmonary lesions on computed tomography were the early clinical manifestations, and the patient developed nonproductive cough later. The hydrothorax in this coronavirus disease 2019 case was exudative, showing predominantly mature lymphocytes.